1990
DOI: 10.1128/jb.172.5.2736-2746.1990
|View full text |Cite
|
Sign up to set email alerts
|

Surface topology of the Escherichia coli K-12 ferric enterobactin receptor

Abstract: Monoclonal antibodies (MAb) were raised to the Escherichia coli K-12 ferric enterobactin receptor, FepA, and used to identify regions of the polypeptide that are involved in interaction with its ligands ferric enterobactin and colicins B and D. A total of 11 distinct FepA epitopes were identified. The locations of these epitopes within the primary sequence of FepA were mapped by screening MAb against a library of FepA::PhoA fusion proteins, a FepA deletion mutant, and proteolytically modified FepA. These exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 47 publications
4
161
0
Order By: Relevance
“…These criteria have been used to devise topological, two-dimensional models for porins (van der Ley et al, 1986;Tommassen, 1988), which were confirmed by the resolution of their crystal structure (Cowan et al, 1992). Similar rules seem to apply to other OMPs (Murphy et al, 1990;Koebnik and Braun, 1993;Brok et al, 1994;Dekker et al, 1995).…”
Section: Introductionmentioning
confidence: 89%
“…These criteria have been used to devise topological, two-dimensional models for porins (van der Ley et al, 1986;Tommassen, 1988), which were confirmed by the resolution of their crystal structure (Cowan et al, 1992). Similar rules seem to apply to other OMPs (Murphy et al, 1990;Koebnik and Braun, 1993;Brok et al, 1994;Dekker et al, 1995).…”
Section: Introductionmentioning
confidence: 89%
“…This condition was met in Triton X-100, but not in DM (k 7 was Ͻ Ͻk 9 ). A possible explanation for this difference is that in DM the rapid release of FeEnt from FepA (k 9 ) results from an active solubilization of the siderophore off the surface of the receptor by the detergent. For release of ColB in the presence of FeEnt, k 10 reflects the ratelimiting step among k 8 , k 6 , k 1 , and k 3 .…”
Section: Fig 4 Time Course Of Ligand Binding In Vitromentioning
confidence: 99%
“…In Vitro Ligand Binding in DM-The mutant protein FepAE280C (6, 10, 12, 31) binds and transports FeEnt, ColB, and ColD at wild type levels. Residue 280 lies in a proposed surface loop that participates in ligand binding (9,10). We derivatized FepAE280C with the sulfhydryl-specific reagent 5-iodoacetamidofluorescein.…”
Section: Feent and Colb Binding Equilibria Inmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure is much more efficient than those previously used to disrupt Streptomyces genes (3). Our approach was based on the discovery that allelic exchanges on the Escherichia coli chromosome can be achieved by recombination with a PCR-generated selectable marker flanked at both ends by extensions of only a few tens of nucleotides homologous to the desired region of the chromosome, when the Red␣ (exo), Red␤ (bet), and Red␥ (gam) proteins of the phage are present in the targeted strain (4)(5)(6)(7)(8)(9). We have used -Red to promote recombination in E. coli between a PCR-amplified antibiotic resistance cassette selectable in E. coli and Streptomyces, and S. coelicolor DNA on a cosmid from the set used to sequence the S. coelicolor genome (10).…”
mentioning
confidence: 99%